Cross-Leg Flaps for Lower Extremity Salvage: A Scoping Review - Van Boerum, Melody Scheefer; Wright, Thomas; McFarland, Mary; Fiander, Michelle; Pannucci, Christopher J. (Journal of Reconstructive Microsurgery, 2019)
Background Lower extremity trauma with soft tissue loss presents a challenge to the reconstructive surgeon. Cross-leg flaps, first described by Hamilton in 1854, are still used to salvage traumatized lower extremities in patients not suitable for free tissue transfer, or those who are receiving care in locations with limited resources.Methods A scoping review methodology was used to examine the evidence supporting the use of cross-leg flaps in modern healthcare.Results There have been 409 cases of cross-leg flaps reported in the modern literature, with the majority of flap cases occurring outside the United States in Turkey, India, and Japan. The most common indication was trauma, mentioned in 93.2% of patients (n = 353 of 379), and anatomic limitation, including inadequate vasculature, was the main reason for not performing free tissue transfer (52.8% of patients; n = 170 of 322). The majority are cross-leg fasciocutaneous flaps (85.8%, n = 273 of 318), based off the posterior tibial artery (27.5%, n = 50 of 182) and peroneal artery (26.9%, n =  49 of 182) and, covering defects of the distal third of the leg (55.5%, n = 151 of 272), or the foot (27.9%, n = 76 of 272). The pedicles are typically divided at 3 weeks (mean 20.9 days) after external fixation is used as the immobilization method (57.7%, n = 184 of 319). Flap survival was 100% across all publications except one (n = 349 of 350 patients), making cross-leg flaps a robust and reliable reconstructive option.Conclusion In resource-limited environments or in patients who are unsuitable for microvascular free tissue transfer, the cross-leg flap remains an impactful and reliable option for limb salvage.
Keywords: lower extremity salvage; cross-leg flap; microvascular